Influence of Religion and Culture on Women’s Rights in Joint Property Settlements in Java, Indonesia - Mahfiana, Layyin; Noor Dzuhaidah Binti Osman; Evi Ariyani; Lutfiana Zahriani (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2025)
Cultural discourse is still dominated by stereotypes that categorize women as second-class citizens with limited roles in the domestic sphere. This view was eroded by modernity but still had implications for minimal protection of women's rights, including in the settlement of joint property after divorce. The hypothesis was that the mechanism for resolving joint property did not provide optimal protection for women's rights due to legal factors, culture biases, and a gender-biased understanding of the law. Therefore, this study examined the problems of resolving joint property through three dimensions, namely (1) Ontological, which showed the inequality of justice for women in the division of joint property, (2) Epistemological, which examined the method of resolution that was still patriarchal due to a lack of understanding of equal rights, partner egoism, and the dominant patriarchal culture, and (3) Axiological, which discussed policy options that were more inclusive and fair for women. The method used was a sociological-empirical (non-doctrinal) analysis of legal regulations, and empirical data from real cases were collected through interviews. This study offered two main innovations, and the first filled a significant gap in the investigation of strategies for resolving joint property that favors women. The second innovation was the preparation of a model affirmative action in the Division of Joint Property as a solution to gender discrimination in law. The results were expected to be the basis for policies and strategies for gender mainstreaming in Islamic family law in Java, Indonesia. Furthermore, this study contributed to uncovering gender inequality in the division of joint property through a holistic method, including ontological, epistemological, and axiological dimensions. Based on empirical data from real-life practices, the result showed that the legal system remained patriarchal and failed to provide optimal protection for women’s rights.